Seven Brief Lessons on Physics - Rovelli, Carlo (Sonipat: Penguin Random House, 2016)
This is a book about the joy of discovery. A playful, entertaining, and mind-bending introduction to modern physics, it's already a major bestseller in Italy and the United Kingdom. Carlo Rovelli offers surprising$1 (Band surprisingly easy to grasp$1 (Bexplanations of general relativity, quantum mechanics, elementary particles, gravity, black holes, the complex architecture of the universe, and the role humans play in this weird and wonderful world. He takes us to the frontiers of our knowledge: to the most minute reaches of the fabric of space, back to the origins of the cosmos, and into the workings of our minds. (3z(BHere, on the edge of what we know, in contact with the ocean of the unknown, shines the mystery and the beauty of the world,(3y (BRovelli writes. (3z(BAnd it$1 (Bs breathtaking.(3ys
Includes index
Keywords: Physics -- Quantum theory -- Relativity; Cosmology -- Time -- Science$1 (BPhilosophys